2016
DOI: 10.1680/macr.14.00402
|View full text |Cite
|
Sign up to set email alerts
|

Punching shear strength of RC flat slabs at interior connections to columns

Abstract: A method to evaluate the punching shear strength of reinforced concrete (RC) flat slabs without shear reinforcement at the connection to interior columns is proposed. The method is based on the assumption that the punching shear strength is controlled by the inclination of a unique punching shear crack that produces a conical failure surface.The inclination angle of the crack is variable. It follows that the location of the critical section is not established in advance, but changes with crack angle. Its locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Before failure, the forces are transferred from the column to the slab through a tri-dimensional strut that develops at variable inclination angles from the root of the column to the tension reinforcement, as a function of the slab thickness, flexural characteristics and material strengths [30]. High stress levels in the strut activate inclined cracking that eventually leads to failure.…”
Section: Kinematics and Failure Modesmentioning
confidence: 99%
“…Before failure, the forces are transferred from the column to the slab through a tri-dimensional strut that develops at variable inclination angles from the root of the column to the tension reinforcement, as a function of the slab thickness, flexural characteristics and material strengths [30]. High stress levels in the strut activate inclined cracking that eventually leads to failure.…”
Section: Kinematics and Failure Modesmentioning
confidence: 99%
“…The dilation angles (ψ) may vary between ψ = 10° for RC corbels [26] to ψ = 40° for RC flat slabs [27,28] as a function of the structural configuration and modes of failure investigated. In this study, as illustrated in Figure 7b, a variation of ψ between 10° and 55°, shows that the best estimates for both peak strength and deformational behaviour are obtained for a dilation angle of ψ = 25°.…”
Section: Constitutive Parametersmentioning
confidence: 99%
“…In the case of slabs without transverse reinforcement, the punching shear failure is characterised by low stresses in the longitudinal reinforcement and the development of a diagonal crack with variable inclination, starting from the root of the column to the tension face of the slab (Figure 2(a)). The inclination of the failure surface is dependent on the reinforcement ratio, slab thickness and material strength and characteristics (Bompa and Oneţ, 2015). When transverse reinforcement is present, the critical crack might intersect the transverse bars and result in yielding of the transverse reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…For the specimens in the present study it was found that the ACI 318-14 design code gives conservative estimates, whereas EC2, Model Code 2010-LoA3 and the CSCT give similar results. A previous study on an extended test database of isolated slab specimens without transverse reinforcement indicated that the punching shear strength decreases with decreasing concrete strength and effective bending depth/isolated member moment span (d/l s ) ratio, and increases with the flexural reinforcement ratio (Bompa and Oneţ, 2015) (the moment span of an isolated slab specimen is the distance between the supports, and is a function of the load arrangement and test setup). In a similar manner, all the tests reported in this paper, regardless of the failure mode, were compared as a function of the varied structural parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation